Dual benefits? Examining how carbon tax influences green investment and government revenue in Indonesia and China - Taufiq, Ahmad; Miftah, Munasiron; Jubaedah, Jubaedah (Educoretax, 2025)
This study aims to analyze the impact of carbon tax implementation on green investment and state tax revenue through a comparative study between Indonesia and China. The carbon tax is considered a policy instrument that not only drives carbon emission reductions but also creates new economic opportunities, particularly in the renewable energy sector. This research employs a qualitative method using content analysis and a scoping review approach to examine secondary data from various international sources. The findings reveal that the implementation of carbon taxes in both countries significantly contributes to the growth of green investment and state revenue. China has demonstrated global leadership through its carbon tax policies supported by substantial investments in renewable energy sectors such as solar and wind power. Conversely, Indonesia, while at an early stage of implementation, exhibits great potential in attracting green investments with more effective policy support and the development of green energy infrastructure. Additionally, carbon taxes contribute to significant carbon emission reductions, as evidenced by studies highlighting the long-term benefits of this policy. This study concludes that the carbon tax functions not only as a fiscal tool to increase state revenue but also as a catalyst for a sustainable green economic transition. Consistent implementation of carbon taxes, supported by policy frameworks and stakeholder collaboration, has the potential to accelerate the transition toward a low-carbon economy in both countries.